A new multiplex real-time polymerase chain reaction assay for the diagnosis of periprosthetic joint infection. Issue 6 (2nd November 2017) - Kawamura, Masaki; Kobayashi, Naomi; Inaba, Yutaka; Choe, Hyonmin; Tezuka, Taro; Kubota, So; Saito, Tomoyuki
Abstract: Objectives: A new multiplex real-time polymerase chain reaction (PCR) assay was developed to detect methicillin-resistant Staphylococcus (MRS) and to distinguish between gram-positive and gram-negative bacteria. In this study, we validated the sensitivity and specificity of this assay with periprosthetic joint infections (PJIs) and evaluated the utility of PCR for culture-negative PJI. Methods: Forty-five samples from 23 infectious PJI cases and 106 samples from 64 non-infectious control cases were analyzed by real-time PCR using a LightCycler Nano ® system. Twenty-eight clinical samples, comprising bacteria of known species isolated consecutively in the microbiological laboratory of our hospital, were used to determine the spectrum of bacterial species that could be detected using the new multiplex primers and probes. Results: The sensitivity and specificity of the MRS- and universal-PCR assays were 92% and 99%, and 91% and 88%, respectively. Twenty-eight species of clinically isolated bacteria were detected using this method and the concordance rate for the identification of gram-positive or gram-negative organisms was 96%. Eight samples were identified as PCR-positive despite a culture-negative result. Conclusion: This novel multiplex real-time PCR system has acceptable sensitivity and specificity and several advantages; therefore, it has potential use for the diagnosis of PJIs, particularly in culture-negative cases.